Measuring Bias against Female Political Leadership. Issue 4 (December 2019) - Setzler, Mark
Abstract: Much research examining gender bias in politics analyzes responses to explicit survey questions asking individuals whether they prefer male over female leaders or agree that male political leaders are superior. Drawing insights from the measurement of other types of prejudice, this article explores the methodological shortcomings of a widely used question of this type. Analyzing the results of two surveys—one national and one state-level—I compare response patterns to a standard, highly explicit question that is frequently administered by the Pew Research Center with those for a modestly altered item that employs multiple strategies to reduce social desirability bias. Compared with the alternative measure, the conventional item seriously underreports prejudice against women leaders. Moreover, the underreporting of bias is especially prevalent among individuals belonging to groups that are strong advocates of gender equality.